Hubungan Tingkat Kepuasan Pasien Terdapat Pelayanan Gizi dengan Sisa Makanan Pasien VIP di Rumah Sakit Panti Rapih Yogyakarta - Bernadeth Dwi Wahyunani; Joko Susilo; Lastmi Wayansari (JURNAL NUTRISIA, 2017)
Background: The success of food service at hospitals could be viewed from patient’s satisfaction. Assessing patient’s satisfaction is one effective, less costly and easy way in maintaining the quality of hospital services. Another indicator of hospital food service quality is the plate waste. The large amount of the plate wasteshows patient’s inadequate nutrient intake and economically speaking it shows waste of resources. Objective: The objective of the research was to gain insight into patient’s level of satisfaction, patient’s plate wasteand the correlation betweenpatient’s level of satisfaction toward food service with the plate waste at the VIP ward at PantiRapih Hospital, Yogyakarta. Method: The research was ananalytical cross-sectional one whose respondents were hospitalized patients in VIP ward and were administered a regular diet (n=50). The data of the plate waste was obtained using visual estimation method by a-6 point scale as developed by Comstock. Patient’s satisfaction toward the food services included taste of food, menu variation, cleanliness and perfection on cutlery, tardiness, staff’s appearance and nutrient education. The data was analyzed using chi-square test. Results: 62% of the respondents were female with the average age of 35. 65% of the respondents had good average ofplate waste. The average plate waste was 24.62%. Breakfast had the highest average of plate waste. It was 31.42%. The type of food with the highest average of plate waste was staple food. It was 35.62%. Patient’s level of satisfaction toward food service was 56%. Conclusion: The statistical analysis using chi-square test did not show any correlation between patient’s level of satisfaction toward food service with patient’splate waste at the VIP ward of PantiRapih Hospital, Yogyakarta. Keywords: plate waste, patient’s satisfaction, Comstock’s visual estimation method, regular diet